Medical Image Tracking Toolbox - Sandro Queirós, Pedro Morais (2020)
Over the years, medical image tracking has gained considerable attention from both medical and research communities due to its widespread utility in a multitude of clinical applications, from functional assessment during diagnosis and therapy planning to structure tracking or image fusion during image-guided interventions. Despite the ever-increasing number of image tracking methods available, most still consist of independent implementations with specific target applications, lacking the versatility to deal with distinct end-goals without the need for methodological tailoring and/or exhaustive tuning of numerous parameters. With this in mind, we have developed the Medical Image Tracking Toolbox (MITT) - a software package designed to ease customization of image tracking solutions in the medical field. While its workflow principles make it suitable to work with 2D or 3D image sequences, its modules offer versatility to set up computationally efficient tracking solutions, even for users with limited programming skills. MITT is implemented in both C/C++ and MATLAB, including several variants of an object-based image tracking algorithm and allowing to track multiple types of objects (i.e. contours, multi-contours, surfaces and multi-surfaces) with several customization features. In this work, the toolbox is presented, its features discussed, and illustrative examples of its usage in the cardiology field provided, demonstrating its versatility, simplicity and time efficiency.